Physiological Responses, Growth, and Yield of Soybean (Glycine max L.) Between Rows of IP-1 Oil Palm in Response to Rhizobium sp. and Bacillus spp. Inoculation - Lugito Lugito; Dyah Weny Respatie; Muhammad Nazmin Yaapar; Eka Tarwaca Susila Putra (Universitas Sebelas Maret, 2025)
The Indonesian population has not yet met the high demand for soybeans by domestic production. Researchers aim to increase soybean (Glycine max L.) production and optimize land use through intercropping with oil palm during the immature plant phase 1 (IP-1). This study evaluated the effectiveness of Rhizobium sp. and Bacillus spp. inoculation in enhancing the growth and yield capacity (physiological activity, growth, and productivity) of soybeans planted between rows of IP-1 oil palms at PT Perkebunan Nusantara (PTPN) IV, Serdang Bedagai Regency, North Sumatera. The field study employed a factorial randomized complete block design (RCBD) with two factors and four blocks as replicates. Data from the experiments were analyzed using analysis of variance (ANOVA), least significant difference (LSD) testing at a 5% significance level, Spearman correlation, and structural equation modeling (SEM). The results showed an interaction effect between Rhizobium sp. and Bacillus spp. inoculation on the treatment variables of plant height, number of leaves, total dry weight, nutrient uptake (N, P, and K), IAA and GA3 hormones, total Bacillus in soil, total Bacillus in roots, pod dry weight, and yield. In treatment without Rhizobium sp., soybean plants inoculated with Bacillus spp. showed a significant contribution to all treatment variables. However, in soybean plants inoculated with Rhizobium sp., the addition of Bacillus spp. did not significantly affect the physiological activity, growth, and yield of soybeans. The performance of Bacillus spp. in boosting the physiological capacity and development of soybeans slowed down in the presence of Rhizobium sp. This indicated a potential antagonistic relationship between Bacillus spp. and Rhizobium sp.